Differential regulation of feeding rhythms through a multiple-photoreceptor system in an avian model of blindness - Valdez, Diego Javier (2013)
All organisms have evolved photodetection systems to synchronize their physiology and behavior with the external light-dark (LD) cycles. In nonmammalian vertebrates, the retina, the pineal organ, and the deep brain can be photoreceptive. Inner retinal photoreceptors transmit photic information to the brain and regulate diverse nonvisual tasks. We previously reported that even after preventing extraretinal photoreception, blind GUCY1* chickens lacking functional visual photoreceptors could perceive light that modulates physiology and behavior. Here we investigated the contribution of different photoreceptive system components (retinal/pineal and deep brain photoreceptors) to the photic entrainment of feeding rhythms. Wild-type (WT) and GUCY1* birds with head occlusion to avoid extraocular light detection synchronized their feeding rhythms to a LD cycle with light >12 lux, whereas at lower intensities blind birds free-ran with a period of >24 h. When released to constant light, both WT and blind chickens became arrhythmic; however, after head occlusion, GUCY1* birds free-ran with a 24.5-h period. In enucleated birds, brain illumination synchronized feeding rhythms, but in pinealectomized birds only responses to high-intensity light (>800 lux) were observed, revealing functional deep brain photoreceptors. In chickens, a multiple photoreceptive system, including retinal and extraretinal photoreceptors, differentially contributes to the synchronization of circadian feeding behavior.—Valdez, D. J., Nieto, P. S., Díaz, N. M., Garbarino-Pico, E., Guido, M. E. Differential regulation of feeding rhythms through a multiplephotoreceptor system in an avian model of blindness.